Perilaku Maternal Dan Kesejahteraan Tapir Asia (Tapirus Indicus) Di Taman Margasatwa Ragunan - Sjahfirdi, Luthfiralda; Ananda, Syafira Dwi (Universitas Al Azhar Indonesia, 2023)
The asian tapir (Tapirus indicus) population continues to decline so the IUCN establishes its conservation status as endangered. One of the conservation efforts that can be done is ex-situ in the zoo. The environmental condition of the zoo is different from their natural habitat which results in asian tapirs having to adapt. One form of adaptation is behavior change that can be experienced by female asian tapir. Behavioral changes such as not wanting to breastfeed can threaten the survival of their offspring. This study aims to identify the maternal behavior of asian tapirs through daytime activities, determine the response of its calf, and determine the welfare of asian tapir in Taman Margasatwa Ragunan (TMR). Observations were made on one female asian tapir and one asian tapir calf. The observation was done from 9.00 to 14.00 during August 2022 and uses the focal animal sampling method. The results show that the mother does more self care than maternal care. Maternal behavior that is carried out are nurse and social. The calf responds by sniffing its mother’s stomach to suckle and approach its mother’s body. The five animal welfare points are fulfilled in asian tapir at TMR.Keywords – Asian tapir, Daily behavior, Maternal care, Tapirus indicus